2013
DOI: 10.1089/thy.2012.0565
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Interferon-Alpha–Induced Thyroid Dysfunction Vary with Ethnicity, Sex, Smoking Status, and Pretreatment Thyrotropin in an International Cohort of Patients Treated for Hepatitis C

Abstract: Biphasic thyroiditis accounted for the majority (58%) of clinically relevant IFNα-induced thyroid dysfunction. We confirmed our recent findings in a related cohort that female sex is a risk factor for thyroiditis but not hypothyroidism. Further, in this large multiethnic study, the risk of thyroiditis is dramatically increased, specifically for white women. Smoking was found to be protective of thyroiditis. These results support closer monitoring of women and those with a serum TSH at the extremes of the norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…This finding could be related to the clinical heterogeneity and to assays and thresholds used that likely contribute to the statistical heterogeneity observed in our study population with the respect to other studies. 26 Moreover, since female sex as well as Caucasic ethnicity represent risk factors for TAI, 40 the relatively high prevalence of TAI in our controls is conceivable. We included in the TAI group women with both normal and impaired thyroid function in accordance with the idea that the presence of anti-thyroid autoantibodies could represent the main factor leading to an increased risk of reproductive failure even in the absence of clinically overt hypothyroidism.…”
Section: Discussionmentioning
confidence: 95%
“…This finding could be related to the clinical heterogeneity and to assays and thresholds used that likely contribute to the statistical heterogeneity observed in our study population with the respect to other studies. 26 Moreover, since female sex as well as Caucasic ethnicity represent risk factors for TAI, 40 the relatively high prevalence of TAI in our controls is conceivable. We included in the TAI group women with both normal and impaired thyroid function in accordance with the idea that the presence of anti-thyroid autoantibodies could represent the main factor leading to an increased risk of reproductive failure even in the absence of clinically overt hypothyroidism.…”
Section: Discussionmentioning
confidence: 95%
“…Risk factors associated with AITD in the setting of IFN- α treatment for HCV include female gender (RR 4.4) as well as the presence of anti-TPO antibodies prior to therapy (RR 3.9); however treatment with IFN- α itself has been associated with the de novo development of anti-TPO antibodies [ 6 ]. Being female and having a higher pretreatment TSH were strongly associated with biphasic thyroiditis, whereas Asian ethnicity and being a current smoker decreased the risk [ 7 ]. Arguably, pretreatment thyroid function may be used to predict those who develop AITD but is undoubtedly indicated in all patients about to commence IFN- α therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Incidence of hyperthyroidism varies among studies as well, with approximately 25% to 60% suffering from transient thyrotoxicosis and the remainder having scintigraphic and/or biochemical evidence of Graves' Hyperthyroidism, many of which required treatment [ 6 ]. In contrast, a large study of 869 HCV patients receiving IFN- α reported biphasic thyroiditis responsible for the majority of AITD cases (58%) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Prummel and Laurberg showed that positive pretreatment AbTPOs are an important risk factor for the development of thyroid dysfunction [74]. There is also an obvious link between female sex, old age, and genetic predisposition with the development of antibodies [75,76].…”
Section: Chc Infection and Thyroid Autoimmunitymentioning
confidence: 99%